When k = 2 ∏ ∞ cos ( 2 k π )
is computed, the result is a π b for integers a and b . What is a + b ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Exactly! Very nice! Thank you, Brian.
Upvoted Brilliant Solution Sir
Sir, Can you please elaborate more the fourth line when we multiply sin , because a lot of things are coming and disappearing which caused a little confusion.
Like: 2 n − 1 s i n ( 2 π )
And also, ⟹ P n = 2 n s i n ( 2 n π ) 2
Log in to reply
As an example, look at P 5 = cos ( 4 π ) cos ( 8 π ) cos ( 1 6 π ) cos ( 3 2 π ) .
Then using the identity I've mentioned in my solution, we see that
sin ( 3 2 π ) ∗ P 5 = cos ( 4 π ) cos ( 8 π ) cos ( 1 6 π ) cos ( 3 2 π ) sin ( 3 2 π ) =
cos ( 4 π ) cos ( 8 π ) cos ( 1 6 π ) ∗ ( 2 1 sin ( 1 6 π ) ) =
cos ( 4 π ) cos ( 8 π ) ∗ ( 4 1 sin ( 8 π ) ) = cos ( 4 π ) ∗ ( 8 1 sin ( 4 π ) ) = 1 6 1 sin ( 2 π ) = 1 6 1 = 2 5 2 .
So in this case P 5 = 2 5 sin ( 2 5 π ) 2 , and in general P n = 2 n sin ( 2 n π ) 2 .
Cos (0) = 1 because 1/infinite
Problem Loading...
Note Loading...
Set Loading...
First look at the finite product P n = k = 2 ∏ n cos ( 2 k π ) for n > 2 .
If we then multiply this by sin ( 2 n π ) , then since sin ( x ) cos ( x ) = 2 sin ( 2 x ) the product will successively "collapse" from the last term to the first, leaving us with the equation
sin ( 2 n π ) ∗ P n = 2 n − 1 sin ( 2 π ) = 2 n 2 ⟹ P n = 2 n sin ( 2 n π ) 2 .
Now lim n → ∞ 2 n sin ( 2 n π ) = lim n → ∞ π ∗ 2 n π sin ( 2 n π ) = π ∗ lim x → 0 x sin ( x ) = π ∗ 1 = π ,
where x = 2 n π → 0 as n → ∞ . Thus
lim n → ∞ P n = π 2 = 2 π − 1 , and so a + b = 2 + ( − 1 ) = 1 .